The Effects of Swimming Training Program on Serum Minerals and Oxidative Stress in Men Aged 20-25 Years - Serdar Adıgüzel; Yeliz Doğru (Journal of Educational Issues, 2024)
In this study, the effects of 8-week swimming training applied to men aged 20-25 on sodium, potassium, magnesium, calcium, unsaturated iron binding capacity (UIBC), iron, CRP, creatinine, bilirubin, albumin parameters were investigated. Ten men with a mean age of 23.07±1.76 years participated in the study. A swimming training program was applied to the participants for 10 weeks/3 days. All tests and measurements were performed before starting the 8-week training program and after completing the 8-week program. The data obtained from the study were analyzed using the SPSS 15.0 package program. The normality distribution of the data was made using the shapiro-wilk test. Participants’ pre-post test measurements were analyzed with the Wilcoxon signed-rank test. According to the results of the data, there was a statistically significant difference between pre-post test data for body weight (BW), sodium, magnesium, creatinine, albumin and bilirubin (p < 0.05). As a result, it can be said that the changes in the minerals and some biochemical parameters necessary for the body with the training programs applied regularly can affect the performance.